TREATMENT OF ABDOMINAL SEPSIS WITH LEVAMISOLE AND PERITONEAL LAVAGE IN RATS - Vieira da Silva, Gabriela; Medeiros de Cunha, Aldo; Medeiros de Azevedo, Ítalo; Medeiros Soares Celani, Lívia; Fernandes Santos de Oliveira , Filipe (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2020)
Introduction: Intra-abdominal sepsis is one of the most difficult situations in surgery and usually presents as a peritonitis. It is a systemic inflammatory response to infection that is often associated with hypoperfusion followed by tissue injury and organ failure. Given that its the sequelae reflect the increasing severity of the systemic response to infection, a correct and early treatment needs to be established. In this sense, the study analyzes the effect of peritoneal lavage and the use of the isomers immunomodulator in the treatment of abdominal sepsis in rats. Methods: The animals were randomly assigned to three groups A (control), B (peritoneal lavage), C (levamisole). All groups underwent laparotomy, anesthesia and cecal ligation/puncture. A ten-parameter clinical score was analyzed, which allowed the classification of sepsis degree, peritoneal fluid cultures, and cytokine dosage. Results: Group C had better scores on the clinical score and also lower growth of bacterial colonies in cultures. A lower dosage of TNF-alpha, IL-Ib, IL-6 and PCR in group C was observed, compared to groups A and B. Conclusion: Levamisole positively influenced the treatment in the parameters analyzed compared to the peritoneal lavage group and the control group.